Current concepts: tissue engineering and regenerative medicine applications in the ankle joint - Correia, Sandra I. (2014)
Tissue engineering and regenerative medicine (TERM) has caused a revolution in present and future trends of medicine and surgery. In different tissues, advanced TERM approaches bring new therapeutic possibilities in either general population as in young patients and high-level athletes, improving restoration of biological functions and rehabilitation. The mainstream components required to obtain a functional regeneration of tissues may include biodegradable scaffolds, drugs or growth factors and different cell types (either autologous or heterologous) that can be cultured in bioreactor systems (in vitro) prior implantation into the patient. Particularly in the ankle, that is subject of many different injuries (e.g. acute, chronic, traumatic, degenerative), there is still no definitive and feasible answer to “conventional” methods. This review aims to provide current concepts of TERM applications to ankle injuries under pre-clinical and/or clinical research applied to skin, tendon, bone and cartilage problems. A particular attention has been given to biomaterials design and scaffolds processing with potential use in osteochondral ankle lesions.